Association of preoperative serum De Ritis ratio with oncological outcomes in patients treated with cytoreductive nephrectomy for metastatic renal cell carcinoma - Laukhtina, Ekaterina; Pradere, Benjamin; D Andrea, David; Rosiello, Giuseppe; Luzzago, Stefano; Pecoraro, Angela; Palumbo, Carlotta; Knipper, Sophie; Karakiewicz, Pierre I; Margulis, Vitaly; Quhal, Fahad; Sari Motlagh, Reza; et al. (Urologic oncology, 2020)
PURPOSE: Identifying which patients are likely to benefit from cytoreductive nephrectomy (CN) for metastatic renal cell carcinoma (mRCC) is important. We tested the association between preoperative serum De Ritis ratio (DRR, Aspartate Aminotransferase/Alanine Aminotransferase) and overall survival (OS) as well as cancer-specific survival (CSS) in mRCC patients treated with CN. MATERIAL AND METHODS: mRCC patients treated with CN at different institutions were included. After assessing for the optimal pretreatment DRR cut-off value, we found 1.2 to have the maximum Youden index value. The overall population was therefore divided into 2 DRR groups using this cut-off (low, <1.2 vs. high, ≥1.2). Univariable and multivariable Cox regression analyses tested the association between DRR and OS as well as CSS. The discrimination of the model was evaluated with the Harrel's concordance index (C-index). The clinical value of the DRR was evaluated with decision curve analysis. RESULTS: Among 613 mRCC patients, 239 (39%) patients had a DRR ≥1.2. Median follow-up was 31 (IQR 16-58) months. On univariable analysis, high DRR was significantly associated with OS (hazard ratios [HR]: 1.22, 95% confidence interval [CI]: 1.01-1.46, P = 0.04) and CSS (HR: 1.23, 95% CI: 1.02-1.47, P = 0.03). On multivariable analysis, which adjusted for the effect of established clinicopathologic features, high DRR remained significantly associated with both OS (HR: 1.26, 95% CI: 1.04-1.52, P = 0.02) and CSS (HR: 1.26, 95% CI: 1.05-1.53, P = 0.01). The addition of DRR only minimally improved the discrimination of a base model that included established clinicopathologic features (C-index = 0.633 vs. C-index = 0.629). On decision curve analysis, the inclusion of DRR did not improve the net-benefit beyond that obtained by established subgroup analyses stratified by IMDC risk groups, type of systemic therapy, body mass index and sarcomatoid features, did not reveal any prognostic value to DRR. CONCLUSION: Despite the statistically significant association between DRR and OS as well as CSS in mRCC patients treated with CN, DRR does not seem to add any further prognostic value beyond that obtained by currently available features.
Keywords: výsledek terapie; nádory ledvin; Male; mRCC; retrospektivní studie; Survival Rate; Cytoreductive nephrectomy; karcinom z renálních buněk; předoperační období; Kidney Neoplasms; CSS; mužské pohlaví; De Ritis ratio; Alanine Transaminase; nefrektomie; Treatment Outcome; Aspartate Aminotransferases; alanintransaminasa; OS; lidé; ženské pohlaví; Humans; Carcinoma, Renal Cell; cytoredukční chirurgie; Preoperative Period; Retrospective Studies; aspartátaminotransferasy; Female; Nephrectomy; Cytoreduction Surgical Procedures; lidé středního věku; míra přežití; Middle Aged